A new species of Craterium (Myxomycetes, Physarales, Physaraceae) with a mottled peridium - Gmoshinskiy, Vladimir I.; Prikhodko, Ilya S.; Novozhilov, Yuri K. (Phytotaxa, 2024)
A new species of Craterium, described herein as С. guttatum, was recovered in Russia, during intensive field work in the Kaluzhskiye Zaseki Nature Reserve (Kaluga Oblast’) and in the Sudogodskiy District of the Vladimir Oblast’. Morphological details of sporocarps and spores were examined by light and scanning electron microscopy. The new species is characterized by a unique combination of morphological characters, such as a beaker-shaped sporotheca with a mottled peridium and a prominent line of dehiscence separating the upper part of the sporotheca in the form of a convex white lid, as well as spores densely ornamented with small warts grouped in clusters. The partial sequences of the 18S rRNA, EF1α and mtSSU genes of C. guttatum differ significantly from all Craterium species sequences available to date.